Variation in Host and Pathogen in the Neonectria/Malus Interaction; toward an Understanding of the Genetic Basis of Resistance to European Canker - Gómez-Cortecero, Antonio; Saville, Robert J.; Scheper, Reiny W. A.; Bowen, Joanna K.; Agripino De Medeiros, Hugo; Kingsnorth, Jennifer; Xu, Xiangming; Harrison, Richard J. (Frontiers in Plant Science, 2016)
Apple canker caused by the phytopathogenic fungus Neonectria ditissima is an economically important disease, which has spread in recent years to almost all pome-producing regions of the world. N. ditissima is able to cross-infect a wide range of apple varieties and causes branch and trunk lesions, known as cankers. Most modern apple varieties are susceptible and in extreme cases suffer from high mortality (up to 50%) in the early phase of orchard establishment. There is no known race structure of the pathogen and the global level of genetic diversity of the pathogen population is unknown. Resistance breeding is underway in many global breeding programmes, but nevertheless, a total resistance to canker has not yet been demonstrated. Here we present preliminary data from a survey of the phylogenetic relationships between global isolates of N. ditissima which reveals only slight evidence for population structure. In addition we report the results of four rapid screening tests to assess the response to N. ditissima in different apple scion and rootstock varieties, which reveals abundant variation in resistance responses in both cultivar and rootstock material. Further seedling tests show that the segregation patterns of resistance and susceptibility vary widely between crosses. We discuss inconsistencies in test performance with field observations and discuss future research opportunities in this area.